Aqueous-ozone irrigation of bone monocortical wounds in hyperglycemic rats - Frascino,Alexandre Viana (2013)
PURPOSE: To analyze the effects of aqueous ozone irrigation over bone healing in hyperglycemia-induced rats. METHODS: Forty-eight male Wistar rats were allocated into Group H (hyperglycemic) or Group N (control). Monocortical bone wound were performed on femurs' anterolateral face. Wounds were treated with a trans-operatory single irrigation of 100ml of aqueous ozone [0.004mg/ml] whereas control groups received 100ml of pure water (Milli-Q®). Histomorphological and histomorphometrical analyses were accomplished after seven, 14 and 21 days. Kruskal-Wallis and Mann-Whitney statistical tests were applied for bone neoformation quantification and assessment. RESULTS: Aqueous ozone wounds irrigated revealed diffuse hemorrhage and increased neoformed of blood vessels number. There was no statistical significant difference in bone trabeculae neoformation. After seven and 14 days, the number of osteoclasts was higher in aqueous ozone groups than in those treated with pure water. CONCLUSION: Independently of blood glucose levels, aqueous ozone allowed an increase in blood vessels neoformation and osteoclast migration, without affect bone trabeculae neoformation.